PERUBAHAN PENGGUNAAN LAHAN DI SEKITAR PASAR MENANGA, KARANGASEM, BALI - I Gede Panca Septiantara; Wahyudi Arimbawa; Wayan Damar Windu Kurniawan (UNHI PRESS, 2022)
The purpose of this study is to understand and describe the phenomenon of land use change that occurs in the area around the Menanga Market. The research method uses qualitative methods, with data analysis techniques carried out by map overlap techniques (overlay). Data was collected by means of field observations and interviews to see and confirm the phenomenon of land use change that occurred at the research location. The results of this study found; First, the change in land use from undeveloped to built with a trend that tends to be in the west and southwest of the Menanga Market; Second, changes in the use of built-up land have turned into trade and service facilities, and changes in non-built land into trade and services have spread on the main road around the Menanga Market. Changes in land use around the Menanga Market are the area of residential land which is increased by 14.92 ha, the use of dry land is reduced by 3.38 ha, and the use of plantation land is decreased by 11.53 ha. Changes in land use in the form of settlements that occur around the Menanga Market are greatest in the west of the Menanga Market. The factors that influence changes in land use and building utilization around the Menanga Market are the increasing community economy, the increasing need for land for settlements, the main road, the existence of the Menanga Market as a village economic center, roads that connect to tourism sites and agglomeration of socio-economic activities around the menanga market.